A review on green synthesis and applications of CeO2 nanomaterials – An eco-friendly approach - P. Vinitha; M.V. Arularasu; R. Vignesh (Chemistry of Inorganic Materials)
Nanotechnology has been introduced in solving global problems in engineering, medicine, science, and pharmacy due to its large surface area-to-volume ratio. Conventional synthesis methods, such as chemical reduction, require hazardous chemicals and are cost-effective. However, green synthesis methods offer an eco-friendly and cost-effective approach. Its ability to easily transition between the Ce³⁺ and Ce⁴⁺ oxidation states, which promotes redox reactions, accounts for its exceptional catalytic activity. Additionally, CeO₂ has remarkable antioxidant properties due to its ability to reduce oxidative stress and scavenge reactive oxygen species (ROS). This review focuses on the green synthesis of CeO2 nanomaterials using various biological sources. The review further covers their emerging applications in photocatalytic dye degradation and potential biological applications along with mechanisms. This review serves as a guide for researchers interested in the green synthesis of CeO2 nanomaterials and recent advances and applications. Improving the functioning of nanoparticles for cutting-edge applications, standardizing synthesis techniques, and expanding biological sources are all areas that hold promise for the future.